A Historical Legacy Untouched by Time and Space? The Hollowing-out of the Norwegian Model of Industrial Relations - Bergene, Ann Cecilie; Hansen, Per Bonde (Nordic Journal of Working Life Studies, 2016)
The Norwegian model of industrial relations has received a lot of praise. It is generally thought of as the pinnacle of the welfare state, a reason why Norway is not severely hit by crises, is highly adaptable, and thus still going strong. This article discusses the historical circumstances in which the model arose with a view to analyze the preconditions for its further existence, arguing that the model must be understood as consisting of, and thus dependent upon, shifting historical subjects. This calls for an analysis of the concrete interactions between various agents, and how it has changed over time and space. In this effort, historical accounts are combined with theories developed within the social sciences in order to explain the dynamics of these interactions. We will argue that the contemporary notion of a Norwegian model of industrial relations, and the accompanying praise, is an ahistorical conceptualization verging on a dogma, and that profound reconfigurations of power relations between the agents of labor and capital need to be taken into account.